Snake Bite: Case Report - Kadriye Kahveci; Dilşen Örnek; İlhami Deimirkapu; Semih Aydemir; Metin Kılınç; Gülten Özgün (Galenos Yayinevi, 2010)
We present a case of a fourty-year-old man who was bitten by a snake on his left leg. It was a severe envenomation with ensuing marked edema and severe pain with complicated coagulation defects. After medical treatment with antivenom and fresh frozen plasma the patient discharged without any complication. (Journal of the Turkish Society of Intensive Care 2010; 8: 73-6)